Opioid Use in Patients With Inflammatory Bowel Disease. Issue 1 (14th February 2020) - Lin, Xiwu; Lofland, Jennifer; Zhang, Ling; Sloan, Sheldon; Chamaa, Laila; Marano, Colleen; Plevy, Scott
Abstract: Background: Data on opioid use in patients with inflammatory bowel disease and the relationship between disease, opioid use, and healthcare resource utilization are needed. Methods: This analysis of real-world data from IBM Watson Health Commercial Claims and Encounters Database included patients with the first claim of inflammatory bowel disease (IBD) between 2007 and 2014. Results: Opioid use was higher in patients with IBD than in the matched non-IBD cohort. Adjusted for age, gender, and Charlson Comorbidity Index score, inpatient and emergency room visits risk was higher in opioid users than non-users in both IBD cohorts. Conclusions: Opioid use could be a potential surrogate for inadequate disease control manifested by increased inpatient and emergency room visit risks. These results suggest a need exists for better disease management and the development of an outcomes measurement tool for IBD pain. Lay Summary: Opioid use, inpatient hospital and emergency room visits were higher in patients with inflammatory bowel disease than a matched non-inflammatory bowel disease cohort. Opioid use could be a potential surrogate for inadequate disease control manifested by increased risk for inpatient hospital and emergency room visits.